Diaspora… tourists? Young Argentine dantzaris and their trips to Euskal Herria (Huellas, 2020)
Diaspora members maintain strong bonds with their homeland. Their trips to the ancestral land are a great opportunity to establish a physical and personal connection with their destination. These bonds, together with extensive knowledge as regards the society and culture of the homeland, make them “feel at home” whenever they visit their homeland. Thus, visits to diaspora members’ homeland represent great challenges related to the way we understand travel and tourism, since they imply special features that differentiate them from other non-diasporic international tourists’ trips. This research focuses on the visits to the Basque Country (Euskal Herria) of young argentine people who practice traditional basque dances. Analysis is carried out on the way these travellers connect with their ancestral place of origin through these trips to the Basque Country. The aim is to discuss up to what extent diaspora members who visit their place of origin can be considered tourists.
Keywords: Basque-Argentine diaspora; Basque Country; Diaspora Tourism